IMPLEMENTASI KURIKULUM BERBASIS KARAKTER DENGAN MEMANFAATKAN POTENSI GAWAI DI SEKOLAH DASAR - Yenny Widyawati; Sutama; Achmad Fatoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to describe the implementation of character-based curriculum utilizing the potential of gadgets at SD N 02 Wukirsawit, Jatiyoso, Karanganyar. The research method used is qualitative with a case study approach. Research participants include teachers, students, parents, and the school principal. Data collection techniques include participant observation, in-depth interviews, and documentation. Data were analyzed using thematic analysis with data triangulation. The results show the importance of implementing a character-based curriculum in facing the digital era, focusing on digital literacy for both teachers and students. Schools need to prepare human resources capable of integrating technology effectively into learning. SD N 02 Wukirsawit has taken initial steps by strengthening digital literacy and utilizing technology resources such as computer laboratories and internet access. In conclusion, the digital character strengthening strategy in this school includes approaches in learning, school environment, and collaboration with parents, aimed at creating a digital-friendly educational environment and preparing students to meet the demands of the times.